Efforts to Handle Cases of Illegal Distribution of Tobacco Products by Gorontalo Customs and Excise Officials (Journal of Civil Criminal Law, 2025)
This research aims to find out and analyze how law enforcement efforts are carried out in cases of distribution of illegal tobacco products by Gorontalo Customs and Excise officials. This research is classified as empirical research using a qualitative approach and then using data collection techniques by means of interviews, literature review, documentation, and using descriptive data analysis. The results of this research indicate that law enforcement efforts against the distribution of illegal tobacco products by Gorontalo Customs and Excise officials include preventive law enforcement (prevention) and repressive law enforcement (Action). In preventive law enforcement Customs and Excise officials carry out legal socialization activities, routine patrol activities and carry out observations, to enforce repressive laws from Customs and Excise officials when they receive information from the intelligence unit or complaints from the public, the data received is then analyzed. If the results of the analysis show that the data meets operational standards then the process of action, deterrence, inspection, sealing and confiscation is continued. Customs and Excise officials in carrying out law enforcement have not yet reached the realm of court, only the imposition of administrative sanctions.